Implementation of Independent Personal Hygiene Practices to Address Self‑Care Deficits in Patients with Schizophrenia - Ramadhani, Fazira Aulia; Rismawan, Wawan (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Schizophrenia is a chronic mental disorder characterized by psychotic behavior, concrete thinking, and difficulties in processing information, affecting cognition, perception, emotion, movement, and behavior. Appropriate management of self-care deficits includes interventions aimed at improving personal hygiene. This study aimed to evaluate the implementation of independent personal hygiene activities on the self-care independence of hospitalized patients with schizophrenia experiencing self-care deficits. This study employed a case report approach. Samples were selected using purposive sampling, and data were collected using a psychiatric nursing care format. The subjects consisted of four patients with schizophrenia who received nursing care including assessment, nursing diagnosis, intervention planning, implementation, and evaluation through the application of Implementation Strategies 1–4 (SP1–SP4). The results of the seven-day intervention showed that patients were able to perform self-care activities, including bathing (hygiene), grooming, eating and drinking, and toileting. These findings suggest that the application of personal hygiene interventions can improve patients’ ability to perform self-care independently. It can be concluded that the implementation of independent personal hygiene activities was successful in achieving good personal hygiene conditions among hospitalized patients with schizophrenia.Keywords: schizophrenia; self-care deficit; personal hygiene; implementation strategy